INTEGRATING ENGLISH AND THE ARTS IN MULTICULTURAL EDUCATION: STRATEGIES FOR INCLUSIVE LEARNING - Resqi Pramana, Andi Dwi (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This article explores the use of English and the arts in the context of multicultural education as a strategy for achieving inclusive learning. The main focus is articulated on the importance of multicultural values in education, as well as the integration of an interdisciplinary approach between language and the arts as a tool for developing students' social and cultural skills. Through literature analysis, surveys, and empirical studies, this article concludes that the integration of multicultural education, the arts, and English not only improves students' academic skills but also fosters tolerance, respect for differences, and the ability to work in diverse environments.